2006
DOI: 10.1016/j.matdes.2004.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of pineapple leaf fibre reinforced polypropylene composites

Abstract: Pineapple leaf fibre, which is rich in cellulose, relative inexpensive and abundantly available has the potential for polymer-reinforced composite. The present study investigates the tensile and flexural behaviours of pineapple leaf fibre-polypropylene composites as a function of volume fraction. The tensile modulus and tensile strength of the composites were found to be increasing with fibre content in accordance with the rule of mixtures. The tensile modulus and tensile strength with a volume fraction 10.8% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
137
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(152 citation statements)
references
References 4 publications
10
137
1
4
Order By: Relevance
“…A yield of 2.1g fibger/100 g pineapple pulp waste has been reported (Sreenath et al, 1996). Furthermore, pineapple leaf fibers are investigated in making fiber-reinforced polymeric composites because of high cellulosic content, abundance and inexpensiveness (Devi et al, 1997;Luo and Netravalli, 1999;Arib et al, 2006). They investigated the tensile, flexural, and impact behavior of pineapple leaf fiber-reinforced polyster composites as a function of fiber loading, fiber length, and fiber surface modification.…”
Section: Ferulic Acidmentioning
confidence: 99%
“…A yield of 2.1g fibger/100 g pineapple pulp waste has been reported (Sreenath et al, 1996). Furthermore, pineapple leaf fibers are investigated in making fiber-reinforced polymeric composites because of high cellulosic content, abundance and inexpensiveness (Devi et al, 1997;Luo and Netravalli, 1999;Arib et al, 2006). They investigated the tensile, flexural, and impact behavior of pineapple leaf fiber-reinforced polyster composites as a function of fiber loading, fiber length, and fiber surface modification.…”
Section: Ferulic Acidmentioning
confidence: 99%
“…Tensile strength of oriented discontinuous fiber composites was evaluated by single fiber pull out showed the fiber/matrix adhesion was good due to the natural waxy surface [16]. Tensile and flexural strength of pineapple leaf fiber reinforced polypropylene composites as a function of volume fraction were found to be increasing with fiber content, in accordance with the rule of mixtures [17]. Straw reinforced polyester composites with volume fraction of 40% resulted in high tensile strength 104 MPa [18].…”
Section: Introductionmentioning
confidence: 92%
“…From the research found, there are fibre in the pineapple leaf. Before this, the fibre from plant leaf are from banana [4]. Environmental awareness, new laws, and legislation are forcing industries to find new materials which are environmental friendly.…”
Section: Introductionmentioning
confidence: 99%